2013
DOI: 10.1524/zpch.2013.0399
|View full text |Cite
|
Sign up to set email alerts
|

Probing Small Protonated Water Clusters in Acetonitrile Solutions by 1H NMR

Abstract: Protonated Water Clusters / Eigen Cation / Zundel Cation / 1 H NMRIn a previous publication by Kalish et al. (J. Phys. Chem. A 115 (2011) 4063) the existence of well defined small protonated water clusters in acetonitrile has been established by IR spectroscopy. Here we report on a 1 H NMR study of triflic acid, CF 3 SO 3 H, in acetonitrile-water solutions. Using NMR we are able to corroborate the general solvation scheme we have proposed for the hydrated proton in acetonitrile as a function of the molar rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 110 publications
(125 reference statements)
4
30
0
1
Order By: Relevance
“…In ref (23) it was proposed that in a system of acid water in acetonitrile with a ratio [H + ]/[H 2 O] = 1:3, the proton is mainly found in between two water molecules (not necessarily in a symmetric configuration), forming a Zundel H 5 O 2 + structure. This finding agrees with the results of earlier linear infrared 25 and 1 H NMR 26 studies and a fs-IR study of the proton transfer mode. 24 Using excitation pulses centered at 2700 cm –1 it was concluded that the excited central OH-stretch vibration of the Zundel-like structure relaxes ultrafast with a time constant T 1 < 65 fs.…”
Section: Introductionsupporting
confidence: 92%
“…In ref (23) it was proposed that in a system of acid water in acetonitrile with a ratio [H + ]/[H 2 O] = 1:3, the proton is mainly found in between two water molecules (not necessarily in a symmetric configuration), forming a Zundel H 5 O 2 + structure. This finding agrees with the results of earlier linear infrared 25 and 1 H NMR 26 studies and a fs-IR study of the proton transfer mode. 24 Using excitation pulses centered at 2700 cm –1 it was concluded that the excited central OH-stretch vibration of the Zundel-like structure relaxes ultrafast with a time constant T 1 < 65 fs.…”
Section: Introductionsupporting
confidence: 92%
“…Thec omparison was made for identical base concentrations,s ot he increasing time delays are mainly because of differences in the reactivities of the bases. Based on steady-state spectroscopic measurements done in the gas phase, [75] and latero ni np rotonated water solvates in acetonitrile solutions, [121,122] we assigned the 1850 and 2570 motifs of the aqueousp roton( deuteron).W ee xclude the possibility of at ransient response of the OÀHs tretching band of HPTS in its photoacid form, since in the absence of the carboxylate bases in D 2 O, we do not observe as ignal withins ignal-to-noise around 1850 cm À1 ,a nd in H 2 O, we have detectedaweaker, featureless response with different transient dynamics. Form arking the time evolution of the reaction intermediate,w eu sed at ransient absorption band that we located for the first time at 1850 cm À1 (Figure 6g).…”
Section: Time-resolved Ultrafast Proton Transfer Dynamics In Acidbasementioning
confidence: 99%
“…[9][10][11] At the current stage of knowledge, it is possible to predict the effect of a mutation on the fate of a particular biosystem, to prove this prediction experimentally, and to explain it theoretically. 12 However, for many formally simple systems experimental results have not been reproduced in silico at a reasonable approximation; the strength of dispersive interactions in solution, 13 spectroscopic signatures of protonated water clusters 14,15 and hydrated hydroxyl anion, 16 the structure of water-base complexes in aprotic solutions 17 and amorphous solids [18][19][20] are among such problems. In such cases, the measured spectral parameters have to be assigned to a certain geometry or energy using empirical correlations.…”
Section: Introductionmentioning
confidence: 99%